Blurring Lines of Responsibility: How Institutional Context Affects Citizen Biases Regarding Policy Problems. (February 2022) - Page, Douglas; Peshkopia, Ridvan
Existing research suggests that individuals assign responsibility for policy problems based on prior biases like partisanship. However, what remains speculation is whether institutions that blur lines of responsibility elicit more biased responsibility-assignment when compared to institutions with clearer lines of responsibility. European Union enlargement provides an opportunity to examine responsibility-assignment for policy problems within multiple countries, where the EU triggers biases (pro- and anti-EU membership) when it works to export the policies required for membership. In surveys of Albania, Bosnia and Herzegovina, and Kosovo, we examine responsibility-assignment to governments for inequality in pay between women and men, which the EU asks prospective members to address. We find that biased attributions of blame for pay inequality are strongest in the Bosnian regions where multilevel governance is the most pronounced, while the unitary governments of Albania, Bosnia's Republika Srpska, and Kosovo do not yield biased responsibility-assignment. Our results are consequential for multilevel governance.